Employee’s Property Rights in China’s State-Owned Enterprise Reorganization - Rong, Tao (Columbia Journal of Asian Law, 1999)
Deteriorating performance by Chinese state-owned enterprises (SOEs) has drained the Government’s financial resources and undermined the economy. Therefore, in the early 1990s, the Chinese government decided to reorganize SOEs in order to promote their efficiency. The first step was to lay off redundant employees to improve the allocation of capital and labor in SOEs.1 The present unemployment law and policies were designed to support massive reallocation of labor and capital in the state-owned economy. At the 15th Chinese Communist Party Congress of August 1997, top leaders formally announced their commitment to intensify massive worker lay-offs from SOEs. Most of these SOEs were to be sold, leased or changed to joint ventures while getting rid of redundant employees. Although tremendous numbers of workers were laid off, SOE managers still complain about the heavy burden of lay-off benefits preventing them recovering from their difficult financial conditions. Creditors of SOEs are extremely worried about large SOE bankruptcy liquidation due to the large amount of workers’ wage arrears and labor reallocation costs that must be paid first and fully before creditors’ conferences. On the other hand, many workers fall into immediate poverty after their discharge. Worker protest actions, claiming property rights from the communist state (that is owned by the working class under the Constitution and Chinese socialist doctrines), are even reported by Chinese domestic media. This Article argues that current Chinese labor law based on socialist economic doctrines, and the property claims to which it gives rise, improperly compensate laid-off SOE workers, thus frustrating the development of a free labor market in China. The first section of this paper elaborates the Chinese socialist labor theories of the employment relationship in SOEs. Section II introduces the Chinese SOEs’ contract employment relationship, which binds together the government, the enterprise, and workers. Section III, explores Chinese SOE workers’ property claims arising under Chinese socialist labor theories, while section IV analyzes the law of SOE employees’ property claims in SOE reorganization. The last section suggests some possible solutions based on studies of market economy and United States employment law.